The Grunt and the Grouch Big splash! - Corderoy, Tracey; Wildish, Lee (North Mankato, Minn Capstone Stone Arch Books, 2012)
In this trio of adventures Grunty and Grouchy, a pair of trolls, always seem to find trouble whatever they are doing
A gift from book Africa
Comic stories
1 2 13 15
NEW_ZTN_GN
Keywords: Humorous stories; Trolls -- Juvenile fiction